Sax's dangerous properties of industrial materials - Lewis, Richard J., Sr., 1939-2018 (John Wiley & Sons, Inc., 2012)
"Since its inception in the early 1950's, this book has become the "bible" for those who need to evaluate the hazard of substances used in commerce. The book contains extensive data on approximately 28,000 substances. It is designed to fill the information needs of professionals who must work with and evaluate the hazards of chemicals"--